2020
DOI: 10.20884/1.jm.2020.15.1.527
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Characterization of Alginate–Chitosan Membranes as Solid Support for BTB and Urease Entrapment

Abstract: A study of alginate-chitosan membrane synthesize was done. The membrane was prepared by mixing alginate hydrosol and chitosan hydrosol at mass ratio of 1:1 and pH of 5.28 approximately. Then it was applied for matrix immobilization of urease and bromothymol blue (BTB) by entrapment technique. The physical, chemical, thermal properties of alginate–chitosan membrane and their impact on immobilized urease activity were investigated. The polymer products were characterized by Fourier Transform Infrared Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Here, carboxylic groups of alginates interact with protonated amine groups of chitosan through ionic interactions to form complexes without the addition of crosslinkers at certain conditions and ratios. It was indicated by FTIR spectra of alginate-chitosan PEC at 1550 cm -1 (NH 3 + ), 1577 cm -1, and 1398 cm -1 (-COO -) (Hermanto et al, 2020;Ismillayli et al, 2020;Kulig et al, 2016). This strong ionic bonding was the main interaction inside the network.…”
Section: Introductionmentioning
confidence: 90%
“…Here, carboxylic groups of alginates interact with protonated amine groups of chitosan through ionic interactions to form complexes without the addition of crosslinkers at certain conditions and ratios. It was indicated by FTIR spectra of alginate-chitosan PEC at 1550 cm -1 (NH 3 + ), 1577 cm -1, and 1398 cm -1 (-COO -) (Hermanto et al, 2020;Ismillayli et al, 2020;Kulig et al, 2016). This strong ionic bonding was the main interaction inside the network.…”
Section: Introductionmentioning
confidence: 90%
“…Here, the morphology of the alginatechitosan membrane mixed was less homogeneous, it can be observed that the transparent membrane surface of the alginate-chitosan shows a fibrous structure with a rough morphology and irregular shape, which is a network of electrostatic interactions of alginate and chitosan. The likeness of its surface morphology has been described at previously work 6,9 .…”
Section: Preparation Of Transparent Pec Membranementioning
confidence: 97%
“…The membrane was prepared from hydrosols of chitosan and alginate, as described by Hermanto et al 6,9 . The scanning electron microscope (SEM) study was carried out on a transparent PEC membrane after being coated with gold palladium on SEM (Joel LV 5600 USA model) to evaluate the morphology and structure of membrane surface, as shown in Fig.…”
Section: Preparation Of Transparent Pec Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in pH and the redox potential of the environment affect the electronic conductivity of the conducting polymer (Gerard et al, 2002). Immobilization of this enzyme in appropriate matrix allows the enzyme was used several times while maintaining its catalytic activity (Hermanto et al, 2020;. In addition, immobilized enzymes on conducting polymer facilitate the electron transfer from the active site of an enzyme that redox reaction takes place to analyte solution, providing good detectability and fast response as redox reaction of the substrate.…”
Section: Introductionmentioning
confidence: 99%